Ammonia-induced mitochondrial impairment is intensified by manganese co-exposure: relevance to the management of subclinical hepatic encephalopathy and cirrhosis-associated brain injury - Heidari, Reza (Clin Exp Hepatol, 2019)
AIM OF THE STUDY: Hepatic encephalopathy (HE) is a neuropsychiatric syndrome ensuing from liver failure. The liver is the major site of ammonia detoxification in the human body. Hence, acute and chronic liver dysfunction can lead to hyperammonemia. Manganese (Mn) is a trace element incorporated in several physiological processes in the human body. Mn is excreted through bile. It has been found that cirrhosis is associated with hyperammonemia as well as body Mn accumulation. The brain is the primary target organ for both ammonia and Mn toxicity. On the other hand, brain mitochondria impairment is involved in the mechanism of Mn and ammonia neurotoxicity. MATERIAL AND METHODS: The current study was designed to evaluate the effect of Mn and ammonia and their combination on mitochondrial indices of functionality in isolated brain mitochondria. Isolated brain mitochondria were exposed to increasing concentrations of ammonia and Mn alone and/or in combination and several mitochondrial indices were assessed. RESULTS: The collapse of mitochondrial membrane potential, increased mitochondrial permeabilization, reactive oxygen species formation, and a significant decrease in mitochondrial dehydrogenase activity and ATP content were evident in Mn-exposed (0.005-1 mM) brain mitochondria. On the other hand, ammonia (0.005-0.5 mM) caused no significant changes in brain mitochondrial function. It was found that co-exposure of the brain mitochondria to Mn and ammonia causes more evident mitochondrial impairment in comparison with Mn and/or ammonia alone. CONCLUSIONS: These data indicate additive toxicity of ammonia and Mn in isolated brain mitochondria exposed to these neurotoxins.